Factors influencing marketable supply of avocado fruit: The case of Lemo Woreda in Hadiya Zone of SNNPR, Ethiopia - Tesfaye, E. (Wachemo University, 2020)
This study intended to determine factors influencing marketable supply of avocado fruit at Lemo woreda in Hadiya zone. The avocado production suffers from many limitations such as, lack of well-organized market system, inadequate skill of post-harvest handling and lack of market information system in the study area. The specific objectives of the study to assess market channel, identifying factors influencing market supply of avocado fruit and examining market supply performance of avocado fruits in the study area. Age, education level, livestock holding, farm size, quantity produce, market information, distance to the nearest market, access for transportation and selling price of produce related positively and negatively with market supply performance of avocado fruit. Multi-stage sampling technique was used to draw the sample of fruit producer farmers. The sample size was 115 farmers/suppliers and 10 traders for crosscheck. Data has been collected using well-structured close ended questionnaires by using enumerators from a randomly selected sample of 115 avocado fruit farmers from Lemo District and cross checking data collected from 10 traders from Hosanna town. The collected data analyzed using Statistical Package for Social Science (SPSS-20); reliability and diagnosis test of the collected data has been checked. Descriptive, correlation and regression analysis has been done. The result reveled that, age, education level, quantity produce, access for market information, access for transportation, distance to the nearest market and selling price of the produce influences market supply performance of avocado fruit at significant level and poor market supply channel, poor market supply performance of avocado fruit in the study area. The study recommends the need for develop market cooperation at the ground level to improve market channel, designing motivation of young farmers’ involvement improve adult learning, improve all factors of marketable supply; thus, to improve market supply performance in the local and distance market uplift the income of the producers and or suppliers.